Leveraging public works for sustainable and resilient livelihoods: Four case studies from India’s Mahatma Gandhi National Rural Employment Guarantee Act - Narayanan, Sudha; Raghunathan, Kalyani; Gautam, Aditi (International Food Policy Research Institute, 2024)
Despite significant improvements in poverty and standard of living over the last two decades, India continues to face challenges, including slow improvements in health and nutrition indicators and in aspects of women’s empowerment and in generating opportunities for sustainable livelihoods. At the same time, climate-related events are increasing in frequency with associated risks. Women and other marginalized populations are often at greater risk from these events due to their relatively lower access to resources, lower mobility and greater dependence on common property resources. Social protection can be an effective instrument to promote resilience. One such large social protection program with significant potential is India’s Mahatma Gandhi National Rural Employment Guarantee Act, or the MGNREGA, one of the largest public works programs in the world.